2006
DOI: 10.1007/s11433-006-0149-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure, spin reorientation and Mössbauer effect studies of Tb0.3Dy0.7(Fe1−x Alx)1.95 alloys

Abstract: The effect of Al substitution for Fe on crystal structure, magnetostriction and spontaneous magnetostriction, anisotropy and spin reorientation of a series of polycrystalline Tb 0.3 Dy 0.7 (Fe 1−x Al x ) 1.95 alloys (x = 0, 0.05, 0.1, 0.15, 0.20, 0.25, 0.30, 0.35) at room temperature and 77 K was investigated systematically. It was found that the primary phase of Tb 0.3 Dy 0.7 (Fe 1−x Al x ) 1.95 is the MgCu 2 -type cubic Laves phase structure when x < 0.4 and the lattice constant a of Tb 0.3 Dy 0.7 (Fe 1−x A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…This formula is used to follow the experimental points and is obtained by a least squares fitting procedure. The border line values of the studied series coincide well with the existing literature data (open points) [22][23][24][25][26][27]. The observed convex deviation a(x) from Vegard's rule, i.e.…”
Section: Materials and X-ray Studiessupporting
confidence: 88%
“…This formula is used to follow the experimental points and is obtained by a least squares fitting procedure. The border line values of the studied series coincide well with the existing literature data (open points) [22][23][24][25][26][27]. The observed convex deviation a(x) from Vegard's rule, i.e.…”
Section: Materials and X-ray Studiessupporting
confidence: 88%
“…Al substitution effect completely destroys the spin exchange coupling between Fe-Fe, R-Fe and R-R when x>0.25 so that Tb 0.3 Dy 0.7-x Pr x (Fe 0.9 Al 0.1 ) 1.95 alloys are of paramagnetism, in which magnetization increases linearly with the external magnetic field. Comparing to the results in our previous investigations [4,10] , we found that Pr substitution improve the Al content of the ferromagnetic alloys. Similarly, Fig.2 indicates that the magnetization is saturated more easily, implying magnetocrystalline anisotropy reduces in the Tb 0.3 Dy 0.7-x Pr x (Fe 0.9 Al 0.1 ) 1.95 alloys.…”
Section: Resultssupporting
confidence: 70%
“…Judging by these research reports, Al is regarded as an ideal substitution for Fe. The application properties of Tb 0.3 Dy 0.7 (Fe 0.9 Al 0.1 ) 1.95 alloys turn out excellent [5][6][7][8][9][10][11] because the addition of Al to Fe increases resistivity and ductility and decreases anisotropy, but its saturated magnetostriction greatly decreases. On the basis of retaining the good application properties, we anticipate that substitution of other elements for Tb or Dy enhances the saturated magnetostriction of Tb 0.3 Dy 0.7 (Fe 0.9 Al 0.1 ) 1.95 alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…. , 0.9 and 1.0) with a cubic, Fd3m, MgCu 2 -type (C15) crystal structure have been previously partially studied elsewhere [18][19][20][21][22][23][24]. The unit cell parameter, for complete data of the series, described by the following numerical formula: a(x) = (−0.104x 2 − 0.029x + 7.337) Å decreases softly non-linearly with cobalt content x [25].…”
Section: Spectra and Analysismentioning
confidence: 99%